The employment effect of technical change : a theoretical study of new technology and the labour market - Katsoulacos, Y. S (Sussex : Harvester Press, 1986)
This book is intended as a contribution to the economic analysis of the employment effects of technical change.The book also offers a survey of existing work in the area of technical change and its effects on employment. The book is divided into two parts dealing with the short run and long run respectively.
Includes bibliographical references and index
ijb, 30/01/2019
Loans
Keywords: Labor supply--Effect of technological innovations on; Labour market